Client Service Satisfaction and Challenges Faced by the Seal of Good Local Governance Awardees - Barangai, Omaimie; Barangai, Omerah (Journal of Interdisciplinary Perspectives, 2024)
This study assessed the level of implementation of the Seal of Good Local Governance (SGLG), the challenges encountered, and client satisfaction in the municipalities of Taraka and Madamba, Lanao del Sur, in 2019. A descriptive-correlational design was employed, involving 220 respondents. The Municipality of Taraka, an SGLG awardee, received a rating of "Qualified" with a mean score of 91.96. At the same time, Madamba, a non-awardee, was rated "Reconsidered/Not Qualified" with a mean score of 57.76 across seven SGLG criteria. The challenges encountered were rated "Moderate" with a mean score of 1.76, while client satisfaction was rated "Satisfied" with a mean value of 3.39. The most common challenges included monitoring public officials, resolving issues through dialogue and socioeconomic conditions, and promoting equal opportunities. Significant relationships were found between the SGLG implementation level, the challenges encountered, and client satisfaction. These findings suggest that client satisfaction and challenges significantly influence SGLG implementation.